Devices for maintenance of comfortable working conditions in floating docks - Shchedrolosiev, O. V.; Uzlov, O. M.; Konovalova, H. V.; Kyrychenko, K. V.; Щедролосев, О. В.; Узлов, О. M.; Коновалова, Г. В.; Кириченко, К. В. (My University, 2018)
Classification of ice-retaining devices has been presented; they allow docking vessels when there is a lot of ice in the water area. Schemes of the devices designed for closing the ends of floating docks are provided. They reduce the amount of draughts on the pontoon deck, which is especially relevant throughout cold autumn, partly winter, and spring. Schemes of the staff structures of dock scaffoldings are presented; the requirements for them are also described.
Пристрої для забезпечення комфортних умов праці при ремонті суден у плавучих доках
Devices for maintenance of comfortable working conditions in floating docks = Пристрої для забезпечення комфортних умов праці при ремонті суден у плавучих доках / O. V. Shchedrolosiev, O. М. Uzlov, H. V. Konovalova, K. V. Kyrychenko // Shipbuilding & Marine Infrastructure. – 2018. – № 1 (9). – P. 134–143.
Keywords: floating dock; ice-retaining device; device for closing the ends of a floating dock; dock scaffoldings; maintenance of working conditions; плавучий док; льодозатримуючий пристрій; пристрій закриття торців дока; докові ліси; забезпечення умов праці